SELF EMPOWERMENT MODEL OF THE POOR IN IMPROVING SOCIAL WELFARE (Studies in the District of Alang-Alang Lebar Palembang, Indonesia) - Siti Rohima; Agus Suman; Asfi Manzilati; Khusnul Ashar (Journal of Indonesian Economy and Business (JIEB), 2013)
Poverty is a very complex problem. So many ways that has been done by the Government but not yet provide optimal results. Any measures taken to overcome poverty often only temporary. There needs to be alternative measures to alleviate poverty through the empowerment one. Self-empowerment for the poor in improving the standard of living and welfare research studies conducted in the District of Alang-Alang Palembang. This study is a qualitative study using interaksionime symbolic approach. In interaksionime symbolic of human behavior and interaction shown by the symbol and meaning, and should be able to translate the meaning and significance of the symbol. This research suggests a model of self-empowerment of the poor through social capital and internal self. In the self-empowerment, poor individuals may act as subjects rather than just the object of poverty reduction. Self-empowerment model in addition supported by a good social capital is also supported by internal self. Internal to include prayer, effort, initiative and tawakal. Self-empowerment is done individually capable of affecting every movement of the poor themselves are to change for improving the living standards and the shackles of poverty, but it can provide motivation to work harder and improve the ethical attitudes and work for productivity increases and is thus able to increase revenue. Empowerment supported by internal social capital and good self will bring individual creativity in doing self-empowerment. This condition can increase income and improve the lives of poor and better than ever before so that poor people more prosperous and achieve the expected welfare.